PENGARUH TINGKAT PENGETAHUAN, PARITAS, JENIS PERSALINAN, JENIS PEKERJAAN TERHADAP FUNGSI SEKSUAL IBU NIFAS - Dwi Masita, Elly (Jurnal Ilmiah Kesehatan (Journal of Health Sciences), 2016)
A preliminary study found 98% of puerperal women decreased sexual function. The aim of research to analyze the effect of the level of knowledge, type of delivery, parity, type of work on sexual function for women. This study used quantitative methods, observational research with cross sectional approach. Sampling techniques used random sampling. The sample size of 150 mother childbirth day 3 to 6 weeks postpartum in the region of BPM Istiqomah, S.Keb.Bid. This study to use questionnaire with multiple linear regression analysis model. There are influence of the level of knowledge on sexual function puerperal women (b = 0.62; CI = 95% = 0:15 to 0.93; p = 0.001). There is the influence of confinement on sexual function puerperal women (b = 1:09; CI = 95% = 0:22 to 1.95; p = 0.014). There parity effect on sexual function puerperal women (b = -1.15; CI = 95% = - 1.96 to -3.39; p = 0.006) There is no effect of the type of work on sexual function in women postpartum (b = 0.62; CI = 95% = 0:03, until 1:21; p = 0.039). The variable that most strongly affect sexual function in primiparous postpartum mothers on day 5- 8 is the level of knowledge (b = 0.62; CI = 95% = 0:15 to 0.93; p = 0.001) and parity (b = -1.15; 95% CI = = - 1.96 to -3.39; p = 0.006). Conclusion: There is the influence of the level of knowledge, parity, type of delivery on sexual function nifasAda maternal parity effect on sexual function, but there was no effect of the type of work on sexual function in women postpartum and the variables that most strongly affect sexual function in primiparous postpartum mothers on day 5- 8 is the level of knowledge and parity.